The Effects Of Moisture On Ovipositional Responses And Larval Eclosion Of Aedes Albopictus - G. M. Saiful, Rahman; Hamady, Dieng; Ahmad, Abu Hassan; Tomomitsu, Satho (The American Mosquito Control Association, 2010)
Moisture plays a major role in the dynamics of mosquito populations, especially those breeding in container habitats. Despite this importance, the role of moisture conditions as they affect oviposition and egg development in Aedes vectors remains largely unexplored. We investigated the effect of exposing gravid female Aedes albopictus mosquitoes and their eggs to different moisture levels (MLs) for various periods on oviposition and hatching. Overall, high-moisture substrates (HMSs; 66% and 72%) provided better environments for egg laying. The timing of initial egg laying was far longer at the lowest substrate moisture level (LSML, 25% and 41.2%) than at HMSs. The numbers of eggs laid were much lower in the drier environments. At LSMLs, gravid females retained increasing numbers of mature eggs until death, and egg retention decreased gradually with increasing ML. The HMSs also provided better environments for larval eclosion. The numbers of eggs hatched were lower at the LSML than the HSML environment. No egg hatching occurred after 1 h exposure to moisture. However, egg hatching occurred by installment, with spontaneous hatching (SH) increasing gradually with increasing ML. High-moisture conditions combined with long exposure (30 h and 48 h) favored SH. These results suggest that Ae. albopictus females can respond to better moisture conditions for increased success of embryonation and larval eclosion. This information may be useful in the colonization of floodwater Aedes species.